Contribution of Angiogenesis to Inflammation and Cancer - Aguilar-Cazares, Dolores; Chavez-Dominguez, Rodolfo; Carlos-Reyes, Angeles; Lopez-Camarillo, César; Hernadez de la Cruz, Olga N.; Lopez-Gonzalez, Jose S. (Frontiers in Oncology, 2019)
During carcinogenesis, advanced tumors are surrounded by both stromal and immune cells, which support tumor development. In addition, inflammation and angiogenesis are processes that play important roles in the development of cancer, from the initiation of carcinogenesis, tumor in situ and advanced stages of cancer. During acute inflammation, vascular hyperpermeability allows inflammatory mediators and immune response cells, including leukocytes and monocytes/macrophages, to infiltrate the site of damage. As a factor that regulates vascular permeability, vascular endothelial growth factor (VEGF) also plays a vital role as a multifunctional molecule and growth factor. Furthermore, stromal and immune cells secrete soluble factors that activate endothelial cells and favor their transmigration to eliminate the aggressive agent. In this review, we present a comprehensive view of both the relationship between chronic inflammation and angiogenesis during carcinogenesis and the participation of endothelial cells in the inflammatory process. In addition, the regulatory mechanisms that contribute to the endothelium returning to its basal permeability state after acute inflammation are discussed. Moreover, the manner in which immune cells participate in pathological angiogenesis release pro-angiogenic factors that contribute to early tumor vascularization, even before the angiogenic switch occurs, is also examined. Also, we discuss the role of hypoxia as a mechanism that drives the acquisition of tumor hallmarks that make certain cancers more aggressive. Finally, some combinations of therapies that inhibit the angiogenesis process and that may be a successful strategy for cancer patients are indicated.